KEBAHAGIAAN DAN AKHIR KEHIDUPAN MENURUT FILSAFAT EKONOMI ISLAM - Harahap, Darwis (HUMAN FALAH: Jurnal Ekonomi dan Bisnis Islam, 2015)
Philosophy is the mother of all sciences. The development of each discipline basically begins with philosophical thinking. Thinking philosophy on an object, thought to the roots of the birth of an object. In a simple philosophy can be defined as thinking in order freely and with deep, so get to the bottom of the issue (Muslih, 1973: 3). In the development of the study of philosophy that gave birth to the science studied scientifically. Sociological developments make knowledge of the results of the study of philosophy into a lifestyle even become worldview (Weltanschauung). This happens not only among scientists but also among ordinary people in general, whether consciously or not, has hegemony by the authority of a particular mindset (Muslih, 1973: 26-27). In realizing the happiness of the world and the hereafter can be extracted from the Quran and Sunnah. In this case, the concept of Islamic economics explore the concept of happiness in the level of economic practice. In the context of Islamic economics, happiness (Falah) is the main aim of the economy. It can be seen from the definition of economics itself, the efforts of the allocation of resources to produce goods and services in accordance with the instructions of Allah to earn His pleasure (Ahmad, 1993: 177), comes with a foundation of morality is very thick, and make falah as the main goal. Maslahah concept is the foundation to solve the problem "relative scarcity" of natural resources and human resources. This will regulate how natural resources are distributed evenly through the consumption of the commodities needed to realize maslahah. Production of the commodity in order to maslahah reached. Distribution of resources and commodities to the public so that every individual can reach maslahah.